2012
DOI: 10.1002/pad.617
|View full text |Cite
|
Sign up to set email alerts
|

Patronage's Progress in Post‐soeharto Indonesia

Abstract: SUMMARYEmpirical evidence and argument concerning governance conditions and human resource management practices indicate that since the fall of Soeharto, patronage has remained a defining feature of the governance of the Indonesian state, resulting in a condition of 'patronage democracy'. Decentralisation together with the symbiotic relationships that can exist between patronage and development assistance have contributed to this. The willingness of factions at the centre to make concessions to competing inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 57 publications
0
63
1
Order By: Relevance
“…According to his observation, fragmentation is visible virtually everywhere, with new or revivified local identities based on ethnicity and religion and with various forms of cultural revival. Additionally, Aspinall (2010) and Peter Blunt et al (2012) show that contemporary Indonesia remains a society of patronage and patronage remains systemic within the government. Notably, money politics and corrupt practices continue to constitute and sustain this patronage (Blunt et al 2012).…”
Section: Perplexed and Assuredmentioning
confidence: 99%
See 1 more Smart Citation
“…According to his observation, fragmentation is visible virtually everywhere, with new or revivified local identities based on ethnicity and religion and with various forms of cultural revival. Additionally, Aspinall (2010) and Peter Blunt et al (2012) show that contemporary Indonesia remains a society of patronage and patronage remains systemic within the government. Notably, money politics and corrupt practices continue to constitute and sustain this patronage (Blunt et al 2012).…”
Section: Perplexed and Assuredmentioning
confidence: 99%
“…Additionally, Aspinall (2010) and Peter Blunt et al (2012) show that contemporary Indonesia remains a society of patronage and patronage remains systemic within the government. Notably, money politics and corrupt practices continue to constitute and sustain this patronage (Blunt et al 2012). In a study of environmental governance, Paruedee Nguitragool (2012) found a lack of large-scale social cohesion between civil society organizations in Indonesia and the public, in conjunction with a fragmentation along the axis of class inequality and identity politics.…”
Section: Perplexed and Assuredmentioning
confidence: 99%
“…Moguls unilaterally abuse their position of political power to suck public resources out of the state or to extort assets from private entities. Examples include politicians diverting state funds directly into party coffers [ [53]: 247], senior bureaucrats running 'semi-formalized' systems whereby positions in the civil service are 'sold' to the highest bidders [7], and military officers being involved in a range of illicit businesses, from illegal logging and mining to protection rackets and smuggling [ [55]: 109].…”
Section: Corruption In East Asiamentioning
confidence: 99%
“…2 Yet, while emerging research work points to the unintended consequences of aid-supported policy transfer for administrative capacity building in non-OECD country contexts (Blunt et al 2012, Karini 2013, the evidence on the role of the "policy community" or "networks" as defi ned in the literature is somewhat anecdotal and continues to remain under-researched (Stone 2004, Pal 2014. Th e Western Balkans, which this paper focuses on, seem to be a case in point, where transfer processes are mainly analyzed -both among policy circles in Brussels and in the fairly limited research work by the regional scholars -within the scope of transfer between the EU as one supranational entity (and lead donor) to individual countries in the region as "benefi ciaries" of its aid to further a specifi c "EU accession" policy transfer.…”
Section: Introductionmentioning
confidence: 99%